A Systematic Review of Meta-Analyses Comparing Periodized and Non-periodized Exercise Programs: Why We Should Go Back to Original Research - Afonso, José; Rocha, Tiago; Nikolaidis, Pantelis T.; Clemente, Filipe Manuel; Rosemann, Thomas; Knechtle, Beat (Frontiers in Physiology, 2019)
Periodization schedules training periods according to predicted timings of cumulative adaptations and has been at the foundation of exercise prescription. Recently, a selected body of work has highlighted that original research may be providing support for variation, but not for periodized variation. Furthermore, it has been suggested that the timings of expected adaptations have not been tested. However, it is not clear if these problems are present in meta-analyses on the subject, since they might have selected a distinct body or work. Therefore, our goal was to systematically review meta-analyses on exercise periodization, to verify whether the included periodized programs have been contrasted to two types of non-periodized programs (i.e., constant or varied) and also if the predictions concerning cumulative adaptations were tested. Data sources: Cochrane, EBSCO (Academic Search Complete, CINAHL Plus, MEDLINE, PsycINFO, SportDISCUS), ISI Web of Knowledge, PEDro, PubMed, Scielo, Scopus. Study eligibility criteria: Meta-analyses comparing periodized exercise programs with non-periodized programs. Participants and interventions: Humans following any form of training periodization. Study appraisal and synthesis methods: A checklist was used to verify whether studies included in the meta-analyses compared periodized to constant or varied, non-periodized programs, as well as whether predictions concerning the timing of adaptations were tested. None of the 21 studies included in the two meta-analyses compared periodized programs with varied, non-periodized programs. The accuracy of the predictions concerning the proposed timings of adaptations was not scrutinized by any of the 21 studies. The studies in question have focused only on strength training, meaning they are limited in scope. The limitations found in these meta-analyses suggest that consultation of original research on the subject is advisable. Systematic review registration number (PROSPERO): CRD42018111338.